2014
DOI: 10.4236/fns.2014.517179
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Total Phenolic Content and Total Antioxidant Activity in Local Red Wines Determined by Spectrophotometric Methods

Abstract: Stratil P., Kubáň V., Fojtová J. (2008): Comparison of the phenolic content and total antioxidant activity in wines as determined by spectrophotometric methods. Czech J. Food Sci., 26: 242-253. Folin-Ciocalteu reagent (FCM) and Price and Butler method (PBM) were used for spectrophotometric determination of the total content of phenolic compounds in 29 wines (8 white, 21 red). The average contents of phenolic compounds determined by FCM and PBM were 108 (90-119) and 105 (90-129) for white wines, and 1545 (874-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 34 publications
5
30
0
1
Order By: Relevance
“…Phenolic compounds can be considered good indicators of antioxidant activity in the fermented products, as their content significantly correlated ( p < 0.01) with antioxidant activity determined by DPPH and FRAP methods. This confirms the major role of phenolic compounds in antioxidant activity .…”
Section: Resultssupporting
confidence: 79%
“…Phenolic compounds can be considered good indicators of antioxidant activity in the fermented products, as their content significantly correlated ( p < 0.01) with antioxidant activity determined by DPPH and FRAP methods. This confirms the major role of phenolic compounds in antioxidant activity .…”
Section: Resultssupporting
confidence: 79%
“…A good correlation between the antioxidant capacity and total phenolic content has been determined in some studies. However, the relationship between individual phenolic componds and antioxidant capacity was unclear (62,63).…”
Section: Comparision Of Antioxidant Capacity and Individual Phenolic mentioning
confidence: 99%
“…They also concluded that besides the previously mentioned antioxidants, antioxidant activity depends not only on the phenolic concentration, but also on the specific chemical structure of each phenolic compound. Previous researches showed good a correlation between the total polyphenols content and antioxidant activity in red wines (Büyüktuncel et al, 2014, Piljac-Ţegarac et al, 2007, while the correlation in white wines varieties was low (Piljac-Ţegarac et al, 2007). As it can be seen (Figures 2 and 3) antioxidant activity shows very bad correlation to polyphenol content regardless of the method used for antioxidant activity determination.…”
Section: Figure 2 Antioxidant Activity In Samples (Abts) Abmentioning
confidence: 92%